Therapeutic Strategies and Clinical Outcome in Papillary Thyroid Microcarcinoma: A Multicenter Observational Study. Issue 3 (2nd September 2016) - Cecoli, F.; Ceresola, E.M.; Altrinetti, V.; Cabria, M.; Cappagli, M.; Montepagani, A.; Cuttica, C.M.; Filippi, U.; Saverino, D.; Raffa, M.; Caputo, M.; Minuto, F.; et al.
Abstract : Purpose: Papillary thyroid microcarcinoma (MPTC) has an excellent prognosis. We aimed to evaluate the evolution of therapeutic strategies over time and the clinical outcome of MPTC. Methods: In this retrospective multicenter observational study in a northwest Italian region, patients with intrathyroidal, unifocal tumor ≤1 cm in size, incidentally found at histology or preoperative cytology diagnosis, were included. Exclusion criteria were a previous head-and-neck irradiation and/or node metastases. Results: From 1985 to 2012, 437 patients had an MPTC diagnosis, which was incidental in 85% and preoperative in 15%. Patients with a preoperative diagnosis were younger at the time of diagnosis (47.6 ± 12.7 years, p < 0.01) and had a larger tumor (7.0 ± 2.5 mm, p < 0.0001) than patients with an incidental diagnosis (age 52 ± 13.5 years, size 4.4 ± 2.8 mm), but there were no differences in clinical outcome between both groups. We observed a significant (p < 0.001) reduction in radioiodine remnant ablation during the years. TSH levels were: <0.1 mIU/l in 27.5%, 0.1-0.5 mlU/l in 33.7%, 0.5-2.5 mlU/l in 32.6%, 2.5-4.2 mlU/l in 3.9%, and >4.2 mlU/l in 2.3% of patients. Six patients (1.37%) had nodal recurrence; 5 of them were cured after therapy. MPTC-linked mortality was null. Conclusions: We confirmed the favorable clinical outcome of MPTC. Despite the reduction in radioiodine ablation, overtreatment of MPTC is still observed.